Epidural blood patch in post-dural puncture headache in parturients: A case series - Shrestha, Babu Raja; Maharjan, Shyam Krishna; Shrestha, Ujma; Moktan, Sushila Lama (Journal of Kathmandu Medical College, 2020)
This is a case series of six obstetric patients who had post-dural puncture headache, resistant to conservative treatment. The onset of post-dural headache in our series on average was on the 34th hour of the procedure. After confirmation of the diagnosis with a typical history of presentation and examination, the patients underwent pharmacological treatment. Post-dural puncture headache, in our series, not relieved by pharmacological treatment underwent epidural blood patch after persistent headache in an average of 5 days post-dural puncture. All patients receiving this therapy had a complete cure of headache at the earliest - from 45 minutes to as late as 11 hours post procedure. Epidural autologous blood instillation in an average of 10 to 11 ml completely relieved the ailment in the primary blood patch. Epidural blood patch is still considered gold standard therapy in persistent post-dural puncture headache.